Measuring trust in vaccination: A systematic review - Larson, Heidi J.; Clarke, Richard M.; Jarrett, Caitlin; Eckersberger, Elisabeth; Levine, Zachary; Schulz, Will S.; Paterson, Pauline (Human vaccines & immunotherapeutics, 2018)
Vaccine acceptance depends on public trust and confidence in the safety and efficacy of vaccines and immunization, the health system, healthcare professionals and the wider vaccine research community. This systematic review analyses the current breadth and depth of vaccine research literature that explicitly refers to the concept of trust within their stated aims or research questions. After duplicates were removed, 19,643 articles were screened by title and abstract. Of these 2,779 were screened by full text, 35 of which were included in the final analysis. These studies examined a range of trust relationships as they pertain to vaccination, including trust in healthcare professionals, the health system, the government, and friends and family members. Three studies examined generalized trust. Findings indicated that trust is often referred to implicitly (19/35), rather than explicitly examined in the context of a formal definition or discussion of the existing literature on trust in a health context. Within the quantitative research analysed, trust was commonly measured with a single-item measure (9/25). Only two studies used validated multi-item measures of trust. Three studies examined changes in trust, either following an intervention or over the course of a pandemic. The findings of this review indicate a disconnect between the current vaccine hesitancy research and the wider health-related trust literature, a dearth in research on trust in low and middle-income settings, a need for studies on how trust levels change over time and investigations on how resilience to trust-eroding information can be built into a trustworthy health system.